Hydrocarbon-associated substrates reveal promising fungi for poly (ethylene terephthalate) (PET) depolymerization - Malafatti-Picca, Lusiane (Braz J Microbiol, 2019)
Recalcitrant characteristics and insolubility in water make the disposal of synthetic polymers a great environmental problem to be faced by modern society. Strategies towards the recycling of post-consumer polymers, like poly (ethylene terephthalate, PET) degradation/depolymerization have been studied but still need improvement. To contribute with this purpose, 100 fungal strains from hydrocarbon-associated environments were screened for lipase and esterase activities by plate assays and high-throughput screening (HTS), using short- and long-chain fluorogenic probes. Nine isolates were selected for their outstanding hydrolytic activity, comprising the genera Microsphaeropsis, Mucor, Trichoderma, Westerdykella, and Pycnidiophora. Two strains of Microsphaeropsis arundinis were able to convert 2–3% of PET nanoparticle into terephthalic acid, and when cultured with two kinds of commercial PET bottle fragments, they also promoted weight loss, surface and chemical changes, increased lipase and esterase activities, and led to PET depolymerization with release of terephthalic acid at concentrations above 20.0 ppm and other oligomers over 0.6 ppm. The results corroborate that hydrocarbon-associated areas are important source of microorganisms for application in environmental technologies, and the sources investigated revealed important strains with potential for PET depolymerization. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s42770-019-00093-3) contains supplementary material, which is available to authorized users.